2016
DOI: 10.1007/s11747-016-0503-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of celebrity endorsements: a meta-analysis

Abstract: Celebrities frequently endorse products, brands, political candidates, or health campaigns. We investigated the effectiveness of such endorsements by meta-analyzing 46 studies published until April 2016 involving 10,357 participants. Applying multilevel meta-analysis, we analyzed celebrity endorsements in the context of for-profit and non-profit marketing. Findings revealed strong positive and negative effects when theoretically relevant moderators were included in the analysis. The most positive attitudinal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
307
4
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(370 citation statements)
references
References 110 publications
8
307
4
17
Order By: Relevance
“…Third, we describe a process and structure for systematic (i.e., non-meta-analytic) review papers, referring to Grewal et al (2018) insights into parallel meta-analytic (effects estimation) review papers. (For some strong recent examples of marketing-related meta-analyses, see Knoll and Matthes 2017;Verma et al 2016). …”
mentioning
confidence: 99%
“…Third, we describe a process and structure for systematic (i.e., non-meta-analytic) review papers, referring to Grewal et al (2018) insights into parallel meta-analytic (effects estimation) review papers. (For some strong recent examples of marketing-related meta-analyses, see Knoll and Matthes 2017;Verma et al 2016). …”
mentioning
confidence: 99%
“…This is another indication of the effectiveness of this type of endorsement. According to Knoll and Matthes (2017), the effectiveness of celebrity endorsement has been discussed in recent years in terms of positive and negative effects, and the influence of this effect is subject to several moderating variables, such as congruence, charisma (Silva et al, 2015) and endorser sex (Bergkvist and Zhou, 2016), which demonstrates the importance of studies that address different aspects and scenarios of this phenomenon.…”
Section: Study 1 -Discussionmentioning
confidence: 99%
“…A meta-analysis performed by Knoll and Matthes (2017) show that studies about the subject have found positive, negative and neutral effects, leaving in doubt the actual effectiveness of celebrity endorsement. The authors demonstrated that the differences found in the studies may have occurred due to moderating variables, such as the endorser type (Wei and Lu, 2013), congruence (Silva et al, 2015) or endorser sex (Bergkvist and Zhou, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations